Impact of Authentic Leadership on Contextual Performance Analytical research in the departments of Foreign Affairs - سعيد, هديل كاظم; حميد, حميد علي (Journal of Economics and Administrative Sciences, 2019)
AbstractThis research aims to examine the correlation and the influence of Authentic Leadership on the contextual performance as a dependent variable, in the departments and Division of the iraqi Ministry of  Foreign Affairs To try out with a number of recommendations that contribute to raising the level of contextual performance in the Ministry. Starting from the importance of research in public organizations and its Role in society, the researcher adopted the descriptive analytical approach in accomplishing this research, The 99 people responded exclusively comprehensively, based on questionnaire that is include 28-item, using interviews and field observations as auxiliary tools in their collection. While the researcher adopted a program(SPSS V.23, Smart PLS, Excel 2010), as well as the use of descriptive statistical methods (the empirical analysis, proportions, arithmetic mean, standard deviation, coefficient of variation, simple linear regression, , Pearson correlation factor). The most important conclusions reached by the researcher are the increase of the influence of the authentic leadership in the contextual performance.  The results of the research founds that the research community deals with the difficulties of working in different ways as a result of having the ability and experience to overcome the difficult circumstances, as well as their expectations of the events because of their confidence in analyzing the problems and their skill to find solutions to them. To match their words with their actions, while understanding the activities and encouraging them to their employees, and tell them the truth of some things is important despite their difficulty. The study concluded with a number of recommendations that reinforce the research variables in the Ministry of Foreign Affairs.